Response of sunflower cultivars to plant density in two planting dates. II. Characteristics associated with harvesting - da Silva, Paulo Regis Ferreira; Rizzardi, Mauro Antônio (Pesquisa Agropecuaria Brasileira, 1993)
This experiment was done in Eldorado do Sul, Rio Grande do Sul, Brazil, in order to evaluate the effects of plant density in two dates of three cultivars of sunflower, on the percent of lodging and/or breaking of plants and other agronomic characteristics associated with mechanized harvest. It also sought to verify the efficiency of the planting date and plant density as management practices to ancicipate harvest date. To do this, the cultivars Contisol 711, Dekalb 180 and GR-10, planted on July 28th and September 18th, 1989, in densities of 30, 50, 70 and 90 thousand plants per ha were used. The increase in plant density reduced the stalk and capitulum diameters. On the other hand, plant height increased with an increased plant density. Independent of plant density, the cultivar of higher stature (GR-10) showed greater lodging than the others. An increase in plant density resulted in earlier flowering, diminished the duration of the subperiod physiological maturation-harvest, as well as speeded up the loss of humidity both in grains and receptacle, independent of the cultivar and of the time of planting. This aspect, associated with precocious seeding (end of July), resulted in an earlier harvest.